STRATEGI PENGEMBANGAN USAHA KERIPIK PISANG PADA INDUSTRI “FLAMBOYAN” DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Sakina, Siti; Tangkesalu, Dance (AGROTEKBIS, 2018)
This research aims to formulate an appropriate business development and can be applied to the development of banana chipsin the industry